Предмет: Алгебра,
автор: nadiart998
Вычислить -(0,002)^-3
-16×2^-4
Ответы
Автор ответа:
1
Сначала умножаем , а потом вычисляем сумму
Приложения:
Автор ответа:
0
Ответ:
-125000001
Объяснение:
-(0,002)^-3 -16*2^-4= -(2/1000)³ -16*(1/2)^4 =
=-(1000/2)³ - 16*1/16= -1000000000/8 - 1=-125000000-1=
=-125000001
Похожие вопросы
Предмет: Другие предметы,
автор: Dennac496
Предмет: География,
автор: bublik5009
Предмет: Физика,
автор: Lolikpolik7652
Предмет: Алгебра,
автор: Kicelikiop
Предмет: Физика,
автор: мастер83